Alkan’s for organ - Michael W. Beauvois (Music & Science, 2018)
Stylistic and pitch-related data derived from the score of Alkan’s Petits Préludes for organ are analyzed using nonparametric correlations and multidimensional scaling, and the results used to reconstruct his compositional process. The reconstruction is then verified by comparing it to an existing cognitive model of musical composition and Alkan’s use of multiple compositional constraints discussed as an example of a strategy employed by master composers to reduce their problem space. The tidy fit of the reconstruction to the model and the agreement of the evidence with a number of previous findings and hypotheses concerning the cognitive processes underlying musical composition strongly suggests that the model and similar analyses of musical variables could be applied to works by other composers and used as a basis for or an adjunct to musicological and psychological studies of the compositional process, particularly when limited to a post hoc analysis or by a finite dataset.